Formation of culture motor activity of pupils of 5-6 classes by means of basic gymnastics - A.H. Deyneko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : methodological conditions justify the use of basic gymnastics in physical education of pupils of secondary schools. The experimental test method creating a culture of motor activity by means of basic gymnastics in the system of physical education students grades 5-9. Material : experiment were selected 109 students. Results : The method comprises three stages: basic, special and profound. The developed method should be applied in the preparatory part of the lesson (15-20 minutes) - invariant component of the curriculum. Found that means basic gymnastics culture is the basis for motor activity. Their conscious and correct implementation is a prerequisite to the motivational desire to exercise. Conclusions : It is proposed to evaluate the physical condition of students with criteria: compliance burden of a preparatory lesson preparedness and age of students; lack of fatigue during exercise basic gymnastics; the impact of stress on technique exercises.